Indoor-Breeding of Aedes albopictus in Northern Peninsular Malaysia and Its Potential Epidemiological Implications - Hamady, Dieng; Rahman G. M., Saifur; Ahmad, Abu Hassan; M. R., Che Salmah; Michael, Boots; Tomomitsu, Satho; Zairi, Jaal; Sazaly, Abubakar (PLoS ONE, 2010)
Background: The mosquito Ae. albopictus is usually adapted to the peri-domestic environment and typically breeds outdoors. However, we observed its larvae in most containers within homes in northern peninsular Malaysia. To anticipate the epidemiological implications of this indoor-breeding, we assessed some fitness traits affecting vectorial capacity during colonization process. Specifically, we examined whether Ae. albopictus exhibits increased survival, gonotrophic activity and fecundity due to the potential increase in blood feeding opportunities. Methodology/Principal Findings: In a series of experiments involving outdoors and indoors breeding populations, we found that Ae. albopictus lives longer in the indoor environment. We also observed increased nighttime biting activity and lifetime fecundity in indoor/domestic adapted females, although they were similar to recently colonized females in body size. Conclusion/Significance: Taken together these data suggest that accommodation of Ae. albopictus to indoor/domestic environment may increase its lifespan, blood feeding success, nuisance and thus vectorial capacity (both in terms of increased vector-host contacts and vector population density). These changes in the breeding behavior of Ae. albopictus, a potential vector of several human pathogens including dengue viruses, require special attention.